Analysis of Noise Strategies for Mosque Buildings in Banda Aceh - Muhammad Joni; Qurratul Aini*; Effendi Nurzal; Cut Putri Nahrisyah (Rumoh Journal of Architecture, 2024)
Noise in mosque buildings is a significant issue affecting the comfort of its users. Mosques are highly sensitive to noise levels, as a calm atmosphere, which is typically found in mosques, requires clear hearing for worship activities. If there is noise disturbance, the function of activities will also be disrupted. The numerous mosque buildings found in the city of Banda Aceh and the increasing density and activity of the surrounding environment will affect its environmental quality, one of which is the noise level. This study aims to examine noise strategies in mosque buildings located in the city of Banda Aceh amidst the rising city activities. The method used is a case study, with the research sample consisting of 10 mosque buildings in Banda Aceh representing nine districts. The results of this study show that most mosques have implemented strategies to reduce noise. The analysis is limited to reviewing the physical elements of the buildings and the environment that affect the noise level.